Equity in Distribution of Health Care Resources; Assessment of Need and Access, Using Three Practical Indicators. - Habib Omrani-Khoo; Farhad Lotfi; Hossein Safari; Sanaz Zargar Balaye Jame; Javad Moghri; Milad Shafii (Tehran University of Medical Sciences, 2013)
Equitable distribution of health system resources has been a serious challenge for long ago among the health policy makers. Conducted studies have mostly ever had emphasis on equality rather than equity. In this paper we have attempted to examine both equality and equity in resources distribution.This is an applied and descriptive study in which we plotted Lorenz and concentration curves to describe graphically the distribution of hemodialysis beds and nephrologists as two complementary resources in health care in relation to hemodialysis patients. To end this, inequality and inequity were measured by calculating Gini- coefficient, concentration and Robin Hood indices. We used STATA and EXCEL software to calculate indicators.The results showed that inequality was not seen in hemodialysis beds in population level. However, distribution of nephrologists without considering population needs was accompanied with some sort of inequality. Gini- coefficient for beds and nephrologists distribution in population level was respectively 0.02 and 0.38. Hence, calculation of concentration index for distribution of hemodialysis beds and nephrologists with regard to population needs indicated that unlike beds distribution, equity gap between nephrologists distribution against patients distribution among the provinces was considerably significant again.Our results imply that although hemodialysis beds in Iran have been distributed in connection with the population need, nephrologists' distribution is not the same as hemodialysis beds one and this imbalance in complementary resources, can affect both efficiency and equitable access to services for population.